BUSINESS FEASIBILITY ANALYSIS OF PATIN FISH ENLARGEMENT POND IN BANUA LAWAS VILLAGE, TABALONG REGENCY - Sahra Wardi Wardi; Ana Zuraida; Inda Ilma Ifada (UPT Publication and Journal Management, Islamic University of Kalimantan, 2023)
This study aims to analyze the Patin fish enlargement pond business in Banua Lawas Village, both from cultivation techniques, production results, revenue, income, profits, and business feasibility. Sampling using the census method with the number of respondents as many as 20. The results showed that the Patin fish enlargement pond business in Banua Lawas Village with 40 ponds with an average seed stocking of 12,100 and a total cost of IDR. 4,220,832,280, the revenue obtained was IDR. 4,299,700,000 with an average of IDR. 214,985,000, the income received was IDR. 513,688,627 with an average of IDR. 25,684,431, the profit obtained in the Patin fish enlargement pond business in Banua Lawas Village was Rp. 78,867,720 with an average of IDR. 3,943,386. The business carried out in Banua Lawas Village is worth working on but has a very small RCR value of 1.02 where every capital spent of IDR. 1 will generate a profit of IDR. 1.02.